Scheduling a Project to Maximise Its Net Present Value: An Integer Programming Approach - Yang, Kum Khiong (Institutional Knowledge at Singapore Management University, 1993)
We describe an integer programming algorithm for determining scheduled start and finish times for the activities of a project subject to resource limitations during each period of the schedule duration. The objective is to maximize the net present value of the project to the firm. A depth-first branch and bound solution procedure searches over the feasible set of finish or completion times for each of the activities of the project. Fathoming criteria based upon the concept of a network cut originally developed to solve the duration minimization version of this problem are extended in this paper to solve the net present value problem. These fathoming decision rules prevent many potentially inferior solutions from being explicitly evaluated. Computational experience reported demonstrates the efficacy of the approach.